The effects of technical nuances of design and construction of laparoscopic instruments on the solution of the problems of surgical treatment of the hepatobiliary zone pathology - Havryliuk , Roman; Maksymenko , Mykhailo; Volkovetsky , Vitalii; Korotia , Mykola (The Ukrainian Scientific Medical Youth Journal, 2024)
the complex nature of the hepatopancreatic zone poses significant surgical problems associated with the prevalence of malignant causes of its pathology, the high complexity of the pertaining surgical interventions, the severity of surgical trauma, and the high level of complications that significantly worsen the quality of life of patients due to the central role of the organs of the hepatopancreatic system in the physiology of the gastrointestinal tract. These reasons create an urgent demand for the improvement of minimally invasive surgical methods intended for surgical interventions in the area of the hepatobiliary and pancreatic zones. Such techniques promise to improve the results of trкeatment of patients, minimize the risks of complications associated with surgical interventions, and significantly reduce the postoperative recovery time. All over the world, laparoscopic approaches to the liver, gallbladder, bile duct, and pancreatic surgery are gaining increasing acceptance, largely due to their ability to minimize the morbidity associated with traditional surgical procedures. This publication presents an overview of new useful models of laparoscopic instruments that favorably change approaches to laparoscopic choledocholithoextraction, facilitate the technical aspects of such interventions, and reduce the risks associated with the use of known instruments for the removal of fixed stones of the common bile duct and dilatation of its sphincter. We highlighted the technical nuances of the design of patented models of laparoscopic instruments, which favorably distinguish them from analogous models, providing a schematic description of characteristic differences in design, and demonstrated their capabilities in solving specific problems associated with the use of analogous instruments offered on the market.